Liquidity and capital requirements and the probability of bank failure - Philipp Johann König (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Using the model of Rochet and Vives (2004), this note shows that a prudential regulator can in general not mitigate a bank's failure risk solely by means of liquidity requirements. However, their effectiveness can be restored if, in addition, minimum capital requirements are met. This provides a rationale for capital requirements beyond the commonly envoked reasoning that they are to be used to control the riskiness of banks' asset portfolios.
Keywords: G21; G28; 330; prudential regulation; liquidity requirements; minimum capital requirements; global games; Bankinsolvenz; Bankenaufsicht; Mindestreservepolitik; Eigenkapitalvorschriften; Bankenliquidität; Spieltheorie; Theorie